Annealing‐Free Platinum−Cobalt Alloy Nanoparticles on Nitrogen‐Doped Mesoporous Carbon with Boosted Oxygen Electroreduction Performance. Issue 15 (13th August 2020) - Huang, Kai; Xu, Pengfu; He, Xian; Wang, Ruyue; Wang, Yonggang; Yang, Hujiang; Zhang, Ru; Lei, Ming; Tang, Haolin
Abstract: Oxygen reduction reaction (ORR) catalysts are critical components for the development of high‐efficiency fuel cells and metal‐air batteries. Supported PtCo alloy nanoparticles (NPs) with modified surface properties and reactivity through ligand, strain and/or ensemble effects are regarded as promising inexpensive low‐Pt candidates. Herein, we report an annealing‐free assembly of PtCo nanoparticles anchored on nitrogen‐doped mesoporous carbon (PtCo@NMC) for advanced ORR electrocatalysis in both alkaline and acidic electrolytes. Compared with the commercial Pt/C catalyst, the half‐wave potential (E1/2 ) values of PtCo@NMC increase to 0.93–0.94 V (Vs. RHE) and positively shift by approximately 45 mV. Moreover, the annealing‐induced degradation stems from agglomeration and growth of alloy NPs. Considering the excellent long‐term durability according to both chronoamperometry (CA) and accelerated durability tests (ADTs), we demonstrate practical application with enhanced performance in electrochemical energy devices, such as a primary Zn–air battery assembled with PtCo@NMC cathode. Abstract : Particle power : PtCo nanoparticles on nitrogen‐doped mesoporous carbon (PtCo@NMC) oxygen reduction reaction (ORR) electrocatalysts consisting of NMC anchored uniformly on PtCo alloy nanoparticles are prepared through a solvothermal reduction followed by annealing‐free solution‐phase loading. This catalyst exhibits higher ORR activity in both acidic and alkaline solutions with respect to commercial Pt/C. The primary Zn‐air battery using the PtCo@NMC catalyst in the cathode further demonstrates practical application in energy conversion and storage devices.